Outsiders in the union: organizing, consent, and union recognition campaigns. (2nd September 2016) - Rooks, Daisy; Penney, Robert A.
Abstract: Although outsiders have played an important role in social protest in the U.S., outsiders' role in the U.S. labor movement has been the focus of spirited debate. Debate about outsider organizers, in particular, reached a fevered pitch in the late 1990s, and continues today. This paper scrutinizes two of the core assumptions of this debate: that insider and outsider organizers operate differently on union recognition campaigns, and that workers respond to them differently in these settings. We analyzed 153 in-depth interviews with workers and organizers conducted at the height of the debate, in order to answer two questions: What is the role of outsider organizers during private sector union recognition campaigns, and how do outsider organizers secure workers' consent in these settings? All of the organizers in our data-set were graduates of the AFL-CIO's Organizing Institute, and 64 of them were outsiders. The outsider organizers in our data-set confronted barriers that insider organizers did not, including workers' concerns about their youth, inexperience and lack of professionalism, and their own inability to relate to workers. While many critics of outsider organizers claim that these barriers are insurmountable, we found the opposite to be true. The vast majority of outsider organizers in our data-set successfully secured workers' consent by demonstrating commitment, building relationships, and being honest and forthright. After proposing changes in organizer training and leadership development in response to these findings, we conclude with a brief discussion of the enduring debate about outsiders' role in social protest in the U.S.